Private‐sector partner selection for public‐private partnership projects of electric vehicle charging infrastructure - Lihui Zhang; Zhenli Zhao; Zhinan Kan (Energy Science & Engineering, 2019)
Abstract Public‐private partnership (PPP) models, which can mitigate the deflection of charging facilities, have been introduced for electric vehicle charging infrastructure (EVCI) projects. Private‐sector partner selection is a significant step to ensure the success of EVCI‐PPP projects, but it has been rarely studied. This paper therefore identifies selection criteria for private partners in EVCI‐PPP projects and assesses the alternatives using an extended multicriteria operation and compromise solution (VIKOR) method. A partner selection indicator system is established through three development processes, and the factors are categorized into five factor packages: basic ability, management ability, performance of previous performance and credit performance, performance of projects, and sustainable development. These factors include 22 subcriteria. An extended VIKOR‐based method incorporating an intuitionistic fuzzy set is developed to select an optimal private partner. A case study is used to verify the effectiveness and rationalization of the proposed approach. Three potential candidates, P1, P2, P3, are evaluated and ranked according to their evaluation scores, and the results show that P1 is the best partner solution. Relevant charging infrastructure project experience, technical level in charging facilities, and financing plan are the top three criteria for choosing appropriate partners for EVCI‐PPP projects. This study provides a comprehensive evaluation framework for the government to select suitable private‐sector partners to accelerate the sustainable development of charging facilities.